Vitality Housing – A Total Solution to Service Transitional Social Housing in Hong Kong. Issue 5 (November 2020) - Lo, T; Lee, K; Rose, E; Seo, B; Au, I
Abstract: In Hong Kong, about two percent of the population lives in squalid, overcrowded housing. Non-Government Organizations (NGOs) advocate that Transitional Social Housing (TSH), which broke the dichotomous housing supply (public vs. private) and can promote changes in Hong Kong's housing system, should be built to provide better quality shelters and supportive services to the underserved group. Scale of economy, efficiency, affordability and sustainability are all keys for success for the TSH program. In this regard, the paper proposes a beacon TSH service model called 'Vitality Housing' as a total solution to equip NGOs with the necessary knowledge to operate and deliver large scale of TSH in Hong Kong. The model suggests: (i) engaging NGOs in design processes to incorporate their needs, (ii) working with design, construction and housing management professionals to adopt cutting-edge technology to reduce life cycle costs, and expediting the TSH delivery, (iii) partnering with asset managers to develop a sustainable financing model for TSH development, and (iv) using a knowledge sharing platform to transfer property development and management knowledge to the NGOs. This model can help local NGOs to learn more efficient approaches to operating TSH based on their expertise in providing social services for the poor.